Analysis of Private Sector Involvement in The Organization of Community-Based Sports Event - Fredy Eko Setiawan; Guntur Ratih Prestifa Herdinata; Aristiyanto, Aristiyanto (Journal Management of Sport, 2025)
The development of community-based sporting events in Indonesia is growing rapidly, driven by increasing public awareness of the importance of healthy lifestyles. However, the sustainability and scale of these events are often constrained by limited funding. Private sector involvement through sponsorship and strategic partnerships is one potential solution to overcome these challenges. This study aims to analyze the forms, motivations, and impacts of private sector involvement in organizing community-based sporting events in Ungaran District, Semarang Regency. Using a qualitative approach with a case study method, data was collected through in-depth interviews with event organizers, private company representatives, and participants. The results show that private sector involvement varies, ranging from direct financial support, provision of products/services, to branding partnerships. The main motivations for companies are brand image enhancement, corporate social responsibility (CSR), and market expansion. On the other hand, event organizers benefit from improved event quality, financial stability, and wider promotional reach. However, challenges such as vision mismatches, complex negotiations, and unmeasured impact evaluations are still encountered. This study concludes that effective collaboration requires transparent communication and a shared vision between both parties.